Pengembangan Modul Berbasis Kearifan Lokal Sumatera Selatan Pembelajaran Tematik Subtema Pekerjaan Orang Tuaku - Herlina, Meilisyah; Faisal; Tastin, Tastin; Syarifuddin, Ahmad (IBTIDA', 2023)
This research aims to find out the process of developing modules based on local wisdom and producing modules based on local wisdom on valid material for theme 4, various jobs, subtheme 3, my parents' jobs, class IV, SD Negeri 09 Kisam Tinggi, South OKU Regency. This type of research is research (R&D) with a model developed by Borg and Gall, with the ADDIE approach method. This research data collection technique uses questionnaires and observation. The results of this research are: the results of the research process in development using processes namely product creation, product validation, revision, and field trials, the validity level of module development is 87%, validation from language experts is 82% and validation from material experts is 82%, thus development is included in the valid category, the level of validity of learning media is 87%, thus development is included in the valid category.